Economic impacts of financialization: evidence for the OECD countries - Rocha, Clara Rita Duarte da (2021)
Financialization translates into an increase in size and the importance of a country's financial sector relative to its overall economy. The financialization literature has been growing in the last decades, and this growth has been more pronounced after 2008, and this work contributes to this branch of literature. The impacts of financialization on economic growth, income inequality and unemployment are measured for the OECD countries using fixed-effect panel regressions. In addition, these impacts were assessed before and after the 2007-2009 crisis. The results seem to indicate that financialization has a negative impact on growth and employment, and there were differences before and after 2008, which were more pronounced in economic growth. In fact, financialization affects macroeconomics and microeconomics, changing the way financial markets are structured and operated and influencing corporate behavior and economic policy, with a negative impact in times of financial crisis.